Does the Ghanaian livelihood empowerment against poverty programme lead to an increase in household productive livelihood assets? Analysing the Ashanti scenario - Peprah, Prince (Cogent social sciences, 2017)
This study draws evidence from 180 respondents who were beneficiaries of the Livelihood Empowerment Against Poverty (LEAP) programme with the underpinning objective of whether the LEAP beneficiaries are able to acquire other productive livelihood assets. Descriptive research involving both quantitative and qualitative methods were used. The study used questionnaires and focus group discussions to obtain data from the respondents. Data were analysed using the descriptive statistics from the SPSS version 17.0 and presented by tables and percentage counts. The study found that the LEAP beneficiaries do not have other preferable productive livelihood assets needed to expand their livelihood options, largely due to the low amount paid coupled with irregularity of payment. The paper therefore recommends that there should be empowerment of beneficiaries with productive capacities through the incorporation of skills and capability development into the programme. This will enhance beneficiary households to initiate new or strengthen old livelihood sources to ensure livelihood sustainability. Moreover, enrolling the LEAP beneficiaries’ caregivers who are not working in a skilled training programme that exists in communities to equip them with livelihood skills which can be used for livelihood activities, such as, baking and soap making will reduce beneficiaries’ dependence on the LEAP cash.